Potret Sikap Toleransi Mahasiswa: Studi Kasus di Politeknik Negeri Ambon - Pradythia Aurellai Nanlohy; Maslan Abdin; Sjafrudin Latar (P3M POLITEKNIK NEGERI AMBON, 2023)
Students are able to appear as vanguards in realizing tolerance and harmony in society, students are inseparable parts of society. Intolerance that occurs in society is a trigger that needs to be resolved. As intellectual beings, students are certainly able to sort out problems objectively and critically. It is these advantages that are expected to be able to give hope for unity in Indonesia. The research aims to analyze and provide an overview of the tolerance attitude of Ambon State Polytechnic students. The research method uses descriptive statistical quantitative analysis. The results of the study found that tolerance showed normal or positive data. This was caused by dividing the value of skewness by the error of skewness where the variable Attitude of Tolerance was 0.565/0.302 = 1.87. This value shows normal because it has a position between -2 and +2. reinforced by survey data in the field showing that the average student who is met disagrees with things that support intolerance and are more supportive of tolerance, so they don't choose things that challenge the tolerance valueKeywords: Tolerance, Attitude, Student